4-(tert-Butyldiphenylsilyloxy)-2,2-dimethylbutanoyl: An Easily Removable Pivaloyl-Type Protecting Group with High Orthogonality - Li, Qishuai; Su, Yong; Qiao, Zhi; Wang, Jianjun; Wang, Peng; Ren, Sumei; Song, Ni; Li, Ming (Synthesis, 2022)
Protecting groups play multiple and vital roles during the synthesis of carbohydrates and other natural products. We herein report the installation and orthogonal cleavage, under mild conditions, of a 4-(tert-butyldiphenylsilyloxy)-2,2-dimethylbutanoyl (BDMB) group as a sterically hindered pivaloyl-type hydroxy protecting group. The compatibility of this substituent with the removal of other protecting groups is also investigated. Due to its advantageous properties, BDMB is anticipated to function as a valuable agent for masking hydroxy groups.
Keywords: 4-(tert-butyldiphenylsilyloxy)-2,2-dimethylbutanoyl; carbohydrates; protecting groups; assisted cleavage; tetrabutylammonium fluoride; acetic acid